If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 2)(x + 10) = 20 Reorder the terms: (2 + X)(x + 10) = 20 Reorder the terms: (2 + X)(10 + x) = 20 Multiply (2 + X) * (10 + x) (2(10 + x) + X(10 + x)) = 20 ((10 * 2 + x * 2) + X(10 + x)) = 20 ((20 + 2x) + X(10 + x)) = 20 (20 + 2x + (10 * X + x * X)) = 20 (20 + 2x + (10X + xX)) = 20 Reorder the terms: (20 + 10X + 2x + xX) = 20 (20 + 10X + 2x + xX) = 20 Add '-20' to each side of the equation. 20 + 10X + 2x + -20 + xX = 20 + -20 Reorder the terms: 20 + -20 + 10X + 2x + xX = 20 + -20 Combine like terms: 20 + -20 = 0 0 + 10X + 2x + xX = 20 + -20 10X + 2x + xX = 20 + -20 Combine like terms: 20 + -20 = 0 10X + 2x + xX = 0 Solving 10X + 2x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2x' to each side of the equation. 10X + 2x + -2x + xX = 0 + -2x Combine like terms: 2x + -2x = 0 10X + 0 + xX = 0 + -2x 10X + xX = 0 + -2x Remove the zero: 10X + xX = -2x Reorder the terms: 10X + 2x + xX = -2x + 2x Combine like terms: -2x + 2x = 0 10X + 2x + xX = 0 The solution to this equation could not be determined.
| -2+9=1x+42 | | 7t+1+5t+8=162 | | -8v+3(v+8)=29 | | -45+15(x)=0 | | -45+15(0)=x | | 4x^3+10x^2-4x-10=0 | | y=-23000+4500x | | -7g=10-6g | | 3x-2y=4x | | -2v-6v=-16 | | 0=4e+4 | | 36-3x=312-x | | 7t+1=162 | | 2x-3+21=-3 | | -45+15(15)=x | | y=2000+2500x-25000+2000x | | 2-(x-3)+6=8 | | 5n+9=54 | | -45+15(1)=x | | a-7a+3=6a+3 | | 1+3n+6=-5 | | (3+3i)+(2+4i)= | | -7w(w-2)=5(3-w) | | 2a^2+5a+18=0 | | 4(u+1)=20 | | x+5-5x=13 | | 5x-23=5x-1 | | 2x^3+5x^2-x-6=0 | | -8x+2=-6 | | 3=x+5-4 | | y+-6x+-9=0 | | (3x^3-24)=0 |